Peningkatan Literasi, Numerasi, dan Teknologi melalui Program Kampus Mengajar di Provinsi Lampung - Muhamad Brilliant; Iis Ariska Nurhasanah (Jurnal Inovasi Pengabdian Masyarakat, 2025)
This community service activity aims to enhance literacy, numeracy, and technological adaptation in learning through the Kampus Mengajar program. The Field Supervisor (DPL) and students conducted a series of collaborative activities at SMKS Amal Bakti Jatimulyo and SMPN Satu Atap 2 Jati Agung, Lampung Province. The implementation used a participatory approach involving teachers, principals, and students in all stages from planning to evaluation. The programs included literacy and numeracy classes, reading corners, literacy trees, Canva training, Quizizz-based learning, and library revitalization. The results showed improved student reading motivation, active participation in learning, and enhanced teacher competence in utilizing digital learning media. Furthermore, the collaboration between universities and partner schools strengthened the implementation of the Tridharma of Higher Education, particularly in community engagement. This activity is expected to serve as a sustainable collaborative model supporting the Merdeka Belajar – Kampus Merdeka initiative at the school level.